Fumitremorgin C Attenuates Osteoclast Formation and Function via Suppressing RANKL-Induced Signaling Pathways - Yuan, Yu; Chen, Kai; Chen, Xi; Wang, Chao; Qiu, Heng; Cao, Zhen; Song, Dezhi; Sun, Youqiang; Guo, Jianmin; Tickner, Jennifer; Xu, Jiake; Zou, Jun (Frontiers in Pharmacology, 2020)
Excessive bone resorption conducted by osteoclasts is considered as the main cause of osteoclast-related bone diseases such as osteoporosis. Therefore, the suppression of excessive osteoclast formation and function is one of the strategies to treat osteoclast-related bone diseases. Fumitremorgin C (Fum) is a mycotoxin extracted from Aspergillus Fumigatus. It has been showed to have extensive pharmacological properties but its role in the treatment of osteoclast-related bone diseases remains unclear. In this study, we aim to find out whether Fum can inhibit receptor activator of nuclear factor‐κB ligand (RANKL)‐induced osteoclast formation and function. The results showed that Fum could significantly attenuate osteoclast formation and function at the concentrations from 2.5 µM to 10 µM. The protein expression of bone resorption factors such as NFATc1, cathepsin K, V‐ATPase‐d2 and c-Fos was suppressed with the treatment of Fum at concentration of 10 µM. In addition, Fum was also shown to suppress the activity of NF-κB, intracellular reactive oxygen species (ROS) level and MAPK pathway. Taken together, the present study showed that Fum could attenuate the formation and function of osteoclast via suppressing RANKL‐induced signaling pathways, suggesting that Fum might be a potential novel drug in the treatment of osteoclast-related bone diseases.